Barbara Walker Sub Urban: New Drawings. (3rd April 2018) - Checinska, Christine
Abstract: British artist Barbara Walker makes drawings of people. She makes drawings of people using charcoal and a soft pencil. She makes drawings of men and women; huge, larger than life, floor to ceiling drawings rendered directly onto the wall. Each fold, crease, line, and blemish of her sitters' bodies and the clothes that enfold them are sensitively transcribed in the smallest of detail. But we never see her sitters' faces. And each wall is wiped clean at the end of every show. It is impossible to view Walker's work without first being astonished by the sheer scale and by the craftsmanship, by the quality of lines seemingly etched into the wall, or the paper, or the canvas, creating a three-dimensional, almost sculptural effect. It comes as no surprise that she sites Giacometti and Rodin as amongst her influences. Yet these soft charcoal and pastel drawings are deeply political. In Walker's hand the methodical making of lines on a wall and the erasing of them is a form of quiet activism. The article published here features drawings from the 2015 exhibition Sub Urban staged at the James Hockey Gallery, Farnham, Surrey, in which Walker examined contemporary stereotypes through the study of the dress codes and fashions adopted by young women.